PLASMA LEPTIN STATUS AND THE RELATIONSHIP BETWEEN DIFFERENT MEDICAL TREATMENTS USED IN ANKYLOSING SPONDYLITIS - Capkin, Erhan; Karkucak, Murat; Akyuz, Ayse; Alver, Ahmet; Ulusoy, Hasan; Karaca, Adem (Oxford Univ Press, 2011)
[Abstract Not Available]
Conference on Excellence in Rheumatology -- FEB 17-19, 2011 -- Istanbul, TURKEY
Keywords: Ankylosing spondylitis; leptin; TNF-alpha